Exploring the additive effect of Ampelopsis grossedentata flavonoids and Tween 80 on feeding Nubian goats - Zhu, Junhong; Lu, Ying; Gao, Zhendong; Chong, Yuqing; Li, Mengfei; Deng, Weidong; Xi, Dongmei (Frontiers in Veterinary Science, 2024)
The ban on antibiotics in animal husbandry underscores the crucial need for safe, natural feed additives. Thirty-two goats were randomly divided into four groups. The control group (CON group) was provided with a basal diet, while the experimental groups received diets supplemented with various dietary additives for a duration of 100 days: either a basal diet supplemented with 25 mg/kg of monensin (MN group), a basal diet containing 2.0 g/kg of Ampelopsis grossedentata flavonoids (AGF group), or a basal diet containing 7.5 mL/kg of Tween 80 (TW group). Blood and rumen fluid samples were collected for analysis at the end of the feeding period. Growth performance was monitored through regular weighing and feed intake measurements. Blood indexes were analyzed using standard biochemical techniques, while the microbial composition of the rumen fluid was determined through high throughput 16S rRNA gene sequencing to assess microbial diversity and function. The effects of the dietary treatments on growth performance, blood indexes, and rumen microbial composition were then evaluated.The AGF group exhibited significantly increased average daily gain, and decreased feed-togain ratio (p < 0.05). Blood indexes analysis revealed no differences between the CON and AGF groups, with both showing higher concentrations of triglyceride, low-density lipoprotein cholesterol, glutamicpyruvic transaminase, alkaline phosphatase, and lactate dehydrogenase compared to the monensin group (p < 0.05). The TW group had significantly higher glucose, glutamic-oxaloacetic transaminase, and glutamic-pyruvic transaminase levels than the MN group (p < 0.05). Microbial diversity analysis revealed that the TW group had significantly greater alpha-diversity than other groups, while betadiversity analysis showed closer similarity between the rumen microbiota of the AGF and CON groups. LEfSe analysis identified Proteobacteria, Deferribacteres, Ehryarchaeoia and Elusimicrobia as biomarkers distinguishing the rumen microbiota among the groups. In conclusion, AGF supplementation increased the relative abundance of beneficial bacteria in the rumen of Nubian goats, and thus enhanced the growth performance. TW supplementation significantly increased rumen microbial diversity and abundance, suggesting benefits for rumen health despite poor palatability. These findings highlight the potential of AGF as a new green additive with important implications for the efficiency and development of animal husbandry.